Trends in prescribing and self-poisoning in relation to UK regulatory authority warnings against use of SSRI antidepressants in under-18-year-olds. - Bergen, H; Hawton, K; Murphy, E; Cooper, J; Kapur, N; Stalker, C; Waters, K (2009)
AIMS: To assess the impact of the UK Medicines and Healthcare products Regulatory Authority (MHRA) warning in December 2003 not to prescribe selective serotonin reuptake inhibitor (SSRI) antidepressants, except fluoxetine, to under-18-year-olds. METHODS: Interrupted time series analysis of prescriptions (UK) and general hospital presentations for nonfatal self-poisoning (three centres in England) for 2000-2006. RESULTS: Following the MHRA warning in December 2003 there were significant decreases in prescribing of SSRI antidepressants (conservative estimate 51%) to young people aged 12-19 years. Surprisingly, this decrease also affected fluoxetine (conservative estimate 20%) and tricyclics (conservative estimate 27%). Nonfatal self-poisoning in this age group following the warning also declined significantly for SSRIs (conservative estimate 44%), but not for fluoxetine, tricyclic antidepressants, or all drugs and other substances. Rates of nonfatal self-harm did not change significantly over the study period. CONCLUSIONS: The reduction in both prescribing and self-poisoning with SSRI antidepressants (except fluoxetine) following the MHRA warning is in keeping with reduced availability of these drugs. There was some evidence of substitution from other SSRIs to fluoxetine for use in self-poisoning. Importantly, overall rates of nonfatal self-harm and self-poisoning did not change, indicating no substitution of method or increases in self-injury.